2018
DOI: 10.1016/j.tust.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A model for predicting smoke back-layering length in tunnel fires with the combination of longitudinal ventilation and point extraction ventilation in the roof

Abstract: An analytical model is developed for quantifying the fire smoke back-layering length in a tunnel with a combination of longitudinal ventilation and point extraction ventilation in the roof. The distance of smoke vent to fire source is incorporated as well as mass flow rate during the whole smoke flow process according to the mass conservation principle. The model input quantities are the heat release rate of the fire source, the longitudinal velocity, the exhaust velocity, the width and the height of the tunne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In 2010, Li et al 12 concluded that the critical ventilation velocity of a road tunnel is proportional to one-third of power of dimensionless heat release rate ( HRR ) under small- or middle-scale fire, while for the large-scale fire, HRR showed limited influence. Since that, the influences of external factors on the critical ventilation velocity have been frequently investigated experimentally and numerically, such as tunnel slope, 1315 aspect ratio, 16,17 vehicle blockage, 1820 smoke exhaust, 21 and fire locations. 22,23 These studies have greatly improved our understanding about critical ventilation velocity for a tunnel fire.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Li et al 12 concluded that the critical ventilation velocity of a road tunnel is proportional to one-third of power of dimensionless heat release rate ( HRR ) under small- or middle-scale fire, while for the large-scale fire, HRR showed limited influence. Since that, the influences of external factors on the critical ventilation velocity have been frequently investigated experimentally and numerically, such as tunnel slope, 1315 aspect ratio, 16,17 vehicle blockage, 1820 smoke exhaust, 21 and fire locations. 22,23 These studies have greatly improved our understanding about critical ventilation velocity for a tunnel fire.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some works have been done to explore the effect of external factors, like the surrounding environment [15,22], exhaust system [30,31] and FFFS (Fixed Fire Fighting Systems) [22]. In Tang et al's [22] study, two series of tests were conducted in ambient temperatures of nearly 10℃ and 30℃ separately in a 1/14 small scaled tunnel.…”
mentioning
confidence: 99%
“…Following these studies, many researchers have studied the effects of several other factors on the back-layering length, and proposed a series of new prediction models, such as tunnel slope [9], cross section [10], turning radius [11], ceiling extraction [12][13][14], branched tunnel [15], and ambient pressure [16][17][18].…”
Section: Hmentioning
confidence: 99%